Tren Kualitas Pelayanan dan Kepuasan Pelanggan Kereta Api Komuter Jurusan Jogja â Solo tahun 2012 Perspektif Komparatif - , AFRIZAL PAHLEVI OCTAVIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to look at the comparison between 2012 to 2014 on customer satisfaction and service quality PT. KAI Operation Region VI Yogyakarta in order to commuter train operation (Prameks, Sriwedari, and Madiun Jaya) Jogja - Solo. The method used in this research is a quantitative descriptive analysis method. This research is done directly by the researchers with the passenger / service users who were on the train commuter Jogja - Solo in 2012 with the data Reforma UGM and 2014 with the primary data. Its population is a commuter train users who have several times using commuter train services in the region of Yogyakarta Operations VI. While the sample is a commuter train service users of Regional Operations VI Yogyakarta region of 100 respondents, the sampling technique used was Convenience sampling. Based on calculations of data in 2012 showed users were satisfied with the quality of commuter train service by 19 percent were satisfied, while users who are not satisfied by 28 percent, compared to the data of 2014 showed satisfied users increased by 34 percent and that users are not satisfied by 17 percent . From 2012 to 2014 according to commuter train users there are three main aspects that need to be diberbaiki are restrictions on the number of passenger, departure schedule accuracy, and timeliness to the destination. Based on data from the year 2012 there are still many users who are not satisfied with the three commuter trains that Prameks by 49.3 percent , 38.6 percent madiun jaya, and Sriwedari 47.5 percent. And the data in 2014 showed more than 50 percent of users are satisfied with the KA Prameks by 50 percent, 76 percent madiun jaya, and Sriwedari by 65.7 percent.